An objective and cross-sectional examination of sun-safe behaviours in New South Wales primary schools - Dean A. Dudley; Wayne G. Cotton; Matthew J. Winslade; Bradley J. Wright; Kirsten S. Jackson; Alexandra M. Brown; Vanessa Rock (BMC, 2017)
Abstract Background Previous evaluations have supported the link between sun protection policies and improved sun protection behaviours. However these evaluations have relied on self-reported data. Methods A cross-sectional design as part of an ongoing 18-month cluster-controlled trial in primary schools (n = 20) was used. Researchers conducted direct observations to record students' hat use and teachers' use of sun protective measures during recess and lunch. Researchers also recorded the volume of sunscreen consumed in each school. Results Only 60% of primary school children wear a sun-safe hat during their breaks when observed using objective measures. Weak correlations were observed between the wearing of a sun-safe hat and a school's socio-economic status (r = 0.26). All other independent variables measured had only very weak correlations (r < 0.19) with sun-safe hat wearing behaviour of students. Sunscreen consumption by school students during the school day is negligible. Conclusions A large percentage of NSW primary schools in this study wear sun-safe hats during the school day but this is well below what has been reported in previous national surveys. Given the finite resources of schools and the correlation, though small, with SES status for these behaviours, it behoves researchers to investigate low-cost solutions to these problems. Further qualitative data will also be needed to inform the enablers and barriers for sun-safe behaviour interventions to be adopted in NSW primary schools.